Novel susceptibility loci for steroid-associated osteonecrosis of the femoral head in systemic lupus erythematosus. Issue 7 (1st December 2021) - Suetsugu, Hiroyuki; Kim, Kwangwoo; Yamamoto, Takuaki; Bang, So-Young; Sakamoto, Yuma; Shin, Jung-Min; Sugano, Nobuhiko; Kim, Ji Soong; Mukai, Masaya; Lee, Yeon-Kyung; Ohmura, Koichiro; Park, Dae Jin; et al.
Abstract: Osteonecrosis of the femoral head (ONFH) involves necrosis of bone and bone marrow of the femoral head caused by ischemia with unknown etiology. Previous genetic studies on ONFH failed to produce consistent results, presumably because ONFH has various causes with different genetic backgrounds and the underlying diseases confounded the associations. Steroid-associated ONFH (S-ONFH) accounts for one-half of all ONFH, and systemic lupus erythematosus (SLE) is a representative disease underlying S-ONFH. We performed a genome-wide association study (GWAS) to identify genetic risk factors for S-ONFH in patients with SLE. We conducted a two-staged GWAS on 636 SLE patients with S-ONFH and 95 588 non-SLE controls. Among the novel loci identified, we determined S-ONFH-specific loci by comparing allele frequencies between SLE patients without S-ONFH and non-SLE controls. We also used Korean datasets comprising 148 S-ONFH cases and 37 015 controls to assess overall significance. We evaluated the functional annotations of significant variants by in silico analyses. The Japanese GWAS identified 4 significant loci together with 12 known SLE susceptibility loci. The four significant variants showed comparable effect sizes on S-ONFH compared with SLE controls and non-SLE controls. Three of the four loci, MIR4293/MIR1265 [odds ratio (OR) = 1.99, P -value = 1.1 × 10 −9 )], TRIM49/NAALAD2 (OR = 1.65, P -value = 4.8 × 10 −8 ) and MYO16 (OR = 3.91, P -value = 4.9 × 10 −10 ), showed significant associations in the meta-analysis with Korean datasets. Bioinformatics analyses identified MIR4293, NAALAD2 and MYO16 as candidate causal genes. MIR4293 regulates a PPARG-related adipogenesis pathway relevant to S-ONFH. We identified three novel susceptibility loci for S-ONFH in SLE.